DETERMINAN KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI - Wahyu Setiyowati, Supami; Emha Fikri Anas, Dimas; Safitri, Arifatul (Distribusi - Journal of Management and Business, 2024)
The principle of accounting conservatism is a cautious approach applied by companies in reporting financial information. This study aims to examine the effect of leverage, cash flow, profitability, capital intensity, and company size on accounting conservatism in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. The method for determining the sample is purposive sampling method so that the sample used includes 26 companies with a sample size of 78. For data analysis using multiple regression analysis equations and hypothesis testing conducted using SPSS 26. The results showed that simultaneously independent variables such as leverage, cashflow, profitability, capital intensity, and company size had an effect on accounting conservatism. While partially leverage and profitability variables have a significant positive effect on accounting conservatism, cashflow variables have a significant negative effect on accounting conservatism, while capital intensity and company size have no significant impact on accounting conservatism.